2022
DOI: 10.1108/jbim-12-2021-0572
|View full text |Cite
|
Sign up to set email alerts
|

Balanced centricity: a joint institutional logic within open collaborative ecosystems

Abstract: Purpose This paper aims to examine the change of institutional logics in actors’ practices within crowdfunding platforms, seen as open collaborative ecosystems. Design/methodology/approach The research follows an abductive approach, wherein data collection and analysis, and the search for complementary theories, constitute parallel iterative processes. A main case study was carried out, complemented by an expert panel. Findings Balanced centricity (BC) as the main institutional logic in crowdfunding platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Since engagement, by definition, does not operate in isolation but rather in a context that implies interaction with other stakeholders, the gaining of experience and co-creative properties (Brodie et al, 2011), so does fundraiser engagement. As indicated earlier, fundraisers interact with platforms, backers and other stakeholders in experiential actions that have implication for value creation at the crowdfunding campaign, product development, venture growth and broader social level (Quero and Mele, 2023;Mastrangelo et al, 2020;Eiteneyer et al, 2019;Smith, 2015).…”
Section: Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Since engagement, by definition, does not operate in isolation but rather in a context that implies interaction with other stakeholders, the gaining of experience and co-creative properties (Brodie et al, 2011), so does fundraiser engagement. As indicated earlier, fundraisers interact with platforms, backers and other stakeholders in experiential actions that have implication for value creation at the crowdfunding campaign, product development, venture growth and broader social level (Quero and Mele, 2023;Mastrangelo et al, 2020;Eiteneyer et al, 2019;Smith, 2015).…”
Section: Engagementmentioning
confidence: 99%
“…, 2011), so does fundraiser engagement. As indicated earlier, fundraisers interact with platforms, backers and other stakeholders in experiential actions that have implication for value creation at the crowdfunding campaign, product development, venture growth and broader social level (Quero and Mele, 2023; Mastrangelo et al. , 2020; Eiteneyer et al.…”
Section: Engagementmentioning
confidence: 99%
“…Importantly Verleye et al (2017) argue that the imbalances can be solved if accountability, communication, engagement and responsiveness between the actor and network level within the service network are fostered, and thus, the goal of balanced centricity is advanced. Furthermore, Quero and Mele (2023) found that adopting balanced centricity as an institutional logic can assist actors in developing a collaborative community, overcoming resource limitations and advancing the cocreation of mutual value. Thus, balanced centricity is a logic that advocates for creation of well-being for all actors, which fosters service system well-being (Leo et al , 2019).…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…This paper argues that balanced centricity is difficult to achieve due to vulnerabilities experienced on multiple levels and among different actors within the service system (Quero and Mele, 2023). The novelty in this is the multilevel and multiactor perspective on experienced vulnerability in service relationships and thus in building sustainable service systems (Groven et al , 2021; Gummesson, 2008).…”
Section: The Way Forward: Contributions For Service Thinking and Prac...mentioning
confidence: 99%